Implementation of the principle ultimum remedium in police action: A juridical analysis of the realization a just and humane lex certa - Sujarwo, Eko (Privietlab, 2026)
The principle of ultimum remedium is a fundamental principle in criminal law that places criminal sanctions as a last resort in law enforcement. This study analyzes the implementation of the principle of ultimum remedium in police action from a fair and humanist lex certa perspective. The research uses normative legal methods with a statutory approach, a case approach, and a theoretical approach. The problems studied include (1) the theoretical conception of the principle of ultimum remedium in the Indonesian criminal law system; (2) the practice of implementing the principle of ultimum remedium in police actions and its challenges; and (3) the ideal construction of the application of the principle of ultimum remedium that is just and humane. The results of the study show that the principle of ultimum remedium has not been fully implemented in police actions due to the unclear norms (lex certa), repressive orientation in law enforcement, and lack of control mechanisms. This study recommends a reformulation of legal provisions that more firmly regulate the principle of ultimum remedium, strengthening the restorative justice approach, and establishing an independent oversight mechanism for police discretion to realize fair and humane law enforcement.